The effect of Effective Microorganism (EM) on growth and yield of paddy / Muhammad Amirul Omar - Omar, Muhammad Amirul (Faculty of Plantation and Agrotechnology, 2018)
Effective Microorganisms (EM) are mixed cultures of beneficial naturally-occurring organisms that can be applied as inoculants to increase the microbial diversity of soil ecosystem. This research was conducted at UiTM campus Jasin with five treatment and 4 replicate. The treatment are T1: 100% NPK, T2: 70%NPK 30%EM, T3: 50%NPK 50%EM, T4: 30%NPK 70%EM, T5: 100%EM. The experimental design used in study is Completely Randomized Design (CRD). The parameters involved in this study are Height of paddy, Number of Tiller, Number of Panicle, Weight of Fresh grain and Weight of Dry grain. The result shown there is significant different between treatment for all parameters. For plant height T2(112.56) shows the highest mean and T5(96.18) shows the lowest mean. For number of Tiller T2(65.91) shows the highest mean and T5(28.59) shows the lowest mean. For number of panicle T2(45.63) shows the highest mean and T5(13.81) shows the lowest mean. For Weight of fresh grain T2(36.73) shows the highest mean and T5(13.68) shows the lowest mean. For Weight of dry grain T2(36.31) shows the highest mean and T5(13.15) shows the lowest mean.